EXPLORATION OF HEALTHY AGEING DETERMINANTS IN BALTIC STATES - Miķelsone, Madara; Baltmane, Diāna; Reine, Ieva; Sniķere, Sigita; Ivanovs, Andrejs; Tomsone, Signe (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
According to the WHO, healthy ageing is characterized by such interrelated determinants as intrinsic capacity, functional ability and environment. An individual's intrinsic capacity is a powerful predictor of the future ageing process and includes 5 areas - cognitive, psychological, sensory, locomotion and vitality. Exploration of these areas can provide necessary information for therapeutic and preventive actions that can be tailored to an individual's needs, priorities and values to support participation and quality of life. The objective of this study was to evaluate and compare healthy ageing determinants of older individuals in the Baltic States. The research was based on the sample of older individuals (50 years and older) from wave 8 of the Survey of Health, Ageing and Retirement in Europe (SHARE) during the period from November 2019 to March 2020. The obtained results indicate a low level/poor results in such determinants as locomotion, sensory, vitality and functional ability (more than 50% of the respondents among the Baltic countries has poor health, various long-term illnesses, limitations in daily activities, suffer from moderate or severe pain, requires help to meet daily needs, etc.), has various behavioral risks, however has higher assessment of cognitive and psychological determinants.